2 mũ x + 2 mũ x+3= 144
2 mũ x-1 + 5.2 mũ x-2= 224
(x-5) mũ 2 = 16
(2x-1) mũ 3 = -64
2 mũ x + 2 mũ x+3 = 144
2 mũ x-1 + 5×2 mũ x-2= 224
(x - 5)2 = 16
=> (x - 5)2 = 42
=> \(\orbr{\begin{cases}x-5=4\\x-5=-4\end{cases}}\)
=> \(\orbr{\begin{cases}x=9\\x=1\end{cases}}\)
(2x - 1)3 = -64
=> (2x - 1)3 = -43
=> 2x - 1 = -4
=> 2x = -4 + 1
=> 2x = -3
=> x = -3/2
( x - 5)2 = 16
=> (x - 5)2 = 42
=> \(\orbr{\begin{cases}x-5=4\\x-5=-4\end{cases}}\)
=> \(\orbr{\begin{cases}x=9\\x=1\end{cases}}\)
123 - 5 . [ x + 4 ] = 38
[ 3x - 2 mũ 4 ] . 7 mũ 3 = 2. 7 mũ 4
5.2 mũ x + 1 = 80
2 mũ x + 2 mũ x + 3 = 576
5 mũ 2x - 3 - 2.5 mũ 2 = 5 mũ 2 .3
12+(5+x)=20
5.2 mũ 2+(x+3)=5 mũ 2
2 mũ 3 +(x+3)=5 mũ 2
4 mũ 3 -(x-2)=5 mũ 2
7 nhân ( x +5 ) + 14 = 7 mũ 3
14 x - 2 nhân 7 mũ 2=2 nhân 3 nhân 7
6 nhân ( x + 2 mũ 3 ) + 40 = 100
155 - 10 nhan ( x +1)=55
12 + ( 5 + x ) = 20 5.22 + ( x + 3 ) = 52 23 + ( x + 3 ) = 52 43 - ( x - 2 ) = 52
17 + x = 20 5.4 + x + 3 = 25 8 + x + 3 = 25 64 - x + 2 = 25
x = 20 - 17 20 + 3 + x = 25 11 + x = 25 66 - x = 25
x = 3 23 + x = 25 x = 25 - 11 x = 66 - 25
x = 25 - 23 x = 14 x = 41
x = 2
Đăng nhìu v bn :) Đáng quan ngại đây :)
Tìm x
8 mũ x = 2 mũ 111
2 mũ x + 5.2 mũ x = 48
2 mũ x + 3.2 mũ x-1 = 40
8x=2111
=>(23)x=2111
=>23x=2111
=>3x=111
=>x=37
2x+5.2x=48
=>2x.6=48
=>2x=8=23
=>x=3
Câu cuối ko làm đc nha
a. 8x = 2111
23x = 2111
3x = 111
x = 111:3
x = 37
b. 2x + 5.2x = 48
2x(5 + 1 )= 48
2x.6 = 48
2x = 48 : 6
2x = 8
2x = 23
x = 3
c. 2x + 3.2x-1 = 40
2x(3:2 +1 ) = 40
2x . \(\frac{5}{2}\) = 40
2x = 40 : \(\frac{5}{2}\)
2x = 16
2x = 24
x = 4
+) \(8^x=2^{111}\)
\(\Rightarrow\left(2^3\right)^x=2^{111}\)
\(\Rightarrow2^{3x}=2^{111}\)
\(\Rightarrow3x=111\)
\(\Rightarrow x=111:3\)
\(\Rightarrow x=37\)
Vậy x = 37
+) \(2^x+5\times2^x=48\)
\(\Rightarrow2^x\times\left(1+5\right)=48\)
\(\Rightarrow2^x\times6=48\)
\(\Rightarrow2^x=48:6\)
\(\Rightarrow2^x=8\)
\(\Rightarrow2^x=2^3\)
\(\Rightarrow x=3\)
Vậy x = 3
+) \(2^x+3\times2^{x-1}=40\)
\(\Rightarrow2^x+3\times2^x:2=40\)
\(\Rightarrow2^x+3\times2^x\times\frac{1}{2}=40\)
\(\Rightarrow2^x+2^x\times\left(3\times\frac{1}{2}\right)=40\)
\(\Rightarrow2^x+2^x\times\frac{3}{2}=40\)
\(\Rightarrow2^x\times\left(1+\frac{3}{2}\right)=40\)
\(\Rightarrow2^x\times\frac{5}{2}=40\)
\(\Rightarrow2^x=40:\frac{5}{2}\)
\(\Rightarrow2^x=16\)
\(\Rightarrow2^x=2^4\)
\(\Rightarrow x=4\)
Vậy x = 4
_Chúc bạn học tốt_
TÌM X
A) 4 MŨ X+2 + 4 MŨ X = 68
B) 5.2 MŨ X+4 - 3.2 mũ x = 308
c) 4.3 mũ x+1 + 7.3 mũ x = 513
d) 5 mũ x+4 - 5 mũ x = 3120
f) 3.4 mũ 2x +1 - 16 mũ x = 2816
bài 2
2 mũ x + 124 = 5 mũ y
cần giúp ạ
Bài 1:
a) \(4^{x+2}+4^x=68\)
\(\Rightarrow4^x\cdot\left(4^2+1\right)=68\)
\(\Rightarrow4^x\cdot17=68\)
\(\Rightarrow4^x=\dfrac{68}{17}\)
\(\Rightarrow4^x=4\)
\(\Rightarrow4^x=4^1\)
\(\Rightarrow x=1\)
b) \(5\cdot2^{x+4}-3\cdot2^x=308\)
\(\Rightarrow2^x\cdot\left(5\cdot2^4-3\right)=308\)
\(\Rightarrow2^x\cdot\left(5\cdot16-3\right)=308\)
\(\Rightarrow2^x\cdot77=308\)
\(\Rightarrow2^x=\dfrac{308}{77}\)
\(\Rightarrow2^x=4\)
\(\Rightarrow2^x=2^2\)
\(\Rightarrow x=2\)
c) \(4\cdot3^{x+1}+7\cdot3^x=513\)
\(\Rightarrow3^x\cdot\left(4\cdot3+7\right)=513\)
\(\Rightarrow3^x\cdot19=513\)
\(\Rightarrow3^x=\dfrac{513}{19}\)
\(\Rightarrow3^x=27\)
\(\Rightarrow3^x=3^3\)
\(\Rightarrow x=3\)
d) \(5^{x+4}-5^x=3120\)
\(\Rightarrow5^x\cdot\left(5^4-1\right)=3120\)
\(\Rightarrow5^x\cdot\left(625-1\right)=3120\)
\(\Rightarrow5^x\cdot624=3120\)
\(\Rightarrow5^x\cdot\dfrac{3120}{624}\)
\(\Rightarrow5^x=5\)
\(\Rightarrow5^x=5^1\)
\(\Rightarrow x=1\)
f) \(3\cdot4^{2x+1}-16^x=2816\)
\(\Rightarrow3\cdot4^{2x+1}-\left(4^2\right)^x=2816\)
\(\Rightarrow3\cdot4^{2x+1}-4^{2x}=2816\)
\(\Rightarrow4^{2x}\cdot\left(3\cdot4-1\right)=2816\)
\(\Rightarrow4^{2x}\cdot11=2816\)
\(\Rightarrow4^{2x}=\dfrac{2816}{11}\)
\(\Rightarrow4^{2x}=256\)
\(\Rightarrow\left(2^2\right)^{2x}=2^8\)
\(\Rightarrow2^{4x}=2^8\)
\(\Rightarrow4x=8\)
\(\Rightarrow x=2\)
Bài 2:
\(2^x+124=5^y\)
\(\Rightarrow5^y-2^x=124\)
\(\Rightarrow5^y-2^x=125-1\)
\(\Rightarrow\left\{{}\begin{matrix}5^y=125\\2^x=1\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}5^y=5^3\\2^x=2^0\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}y=3\\x=0\end{matrix}\right.\)
Vậy: ....
Tìm X:
a, 25 + 3 ( x-8 ) = 106
b, 3 mũ 2 ( x+4 ) - 5 mũ 2 = 5.2 mũ 2
Tìm X:
a, 25 + 3 ( x-8 ) = 106
b, 3 mũ 2 ( x+4 ) - 5 mũ 2 = 5.2 mũ 2
3.(x-8) = 106-25
3.(x-8) = 81
x-8 = 81:3
x-8 = 27
x=35
\(a,25+3\left(x-8\right)=106\\ 3\left(x-8\right)=81\\ x-8=27\\ x=35\)
32 . (x + 4 ) - 52 = 5 . 22
9 . ( x + 4 ) - 25 = 20
9 . ( x + 4 ) = 20 + 25
9 . ( x + 4 ) = 45
( x + 4 ) = 45 : 9
x + 4 = 5
x = 5 - 4
x = 1
3 mũ 2 .(x+14)- 5 mũ 2 =5.2 mũ 2
5.2 mũ x+1.2 mũ -2-2 mũ x=384
\(5\cdot2^x+1\cdot2^{x-2}-2^x=384\)
=>\(4\cdot2^x+2^x\cdot\dfrac{1}{4}=384\)
=>2^x=1536/17
hay \(x\in\varnothing\)